2020
DOI: 10.1097/won.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

Stoma-Related Complications Following Ostomy Surgery in 3 Acute Care Hospitals

Abstract: PURPOSE: The aim of this study was to evaluate both surgical and patient-centered stomal complications after stoma formation, with emphasis on underreported symptoms and complaints. DESIGN: Prospective, single-group study. SUBJECTS AND SETTING: Patients undergoing emergency and elective ostomy surgery between January 1, 1999, and June 1, 2016, in 3 acute care hospitals were followed up by stoma care nurse sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 39 publications
6
50
0
Order By: Relevance
“…Impairments of health-related quality of life (HRQoL) [7,8] are also reported but may differ [9] due to the diverse social and health care situations across countries [10]. A growing body of literature has documented the occurrence of a range of stoma-related complications within the early years of stoma formation [11,12]. Stenosis, parastomal hernia, and stomal prolapse are examples of frequently reported complications [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Impairments of health-related quality of life (HRQoL) [7,8] are also reported but may differ [9] due to the diverse social and health care situations across countries [10]. A growing body of literature has documented the occurrence of a range of stoma-related complications within the early years of stoma formation [11,12]. Stenosis, parastomal hernia, and stomal prolapse are examples of frequently reported complications [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Stoma-related complications are common and can be classified as early or late. The rates of stoma complications reported in the literature vary widely, ranging from 10 to 70% [ 7 , 9 , 10 ]. The risk for complications from stoma creation is lifelong, although complications have been reported to be most frequent in the first 5 years postoperatively [ 7 , 9 ].…”
Section: Main Textmentioning
confidence: 99%
“…Common early complications include leakage and skin irritations, high output resulting in fluid and electrolyte imbalances, or stoma necrosis; late complications include parastomal hernia, stoma prolapse, and stoma stenosis [ 7 ]. These can develop as a result of surgical- or patient-related factors (Table 2 ) [ 2 , 10 12 ].…”
Section: Main Textmentioning
confidence: 99%
“…A parastomal hernia occurs when there is a protrusion of bowel contents through the fascial defect in the abdominal wall. They are extremely common and a recent study has demonstrated a parastomal hernia rate of 34.5% at 2 years (Pearson et al., 2020). Patients will usually present with a bulge around their stoma site.…”
Section: Stoma Complicationsmentioning
confidence: 99%